2019
DOI: 10.5194/nhess-2019-10
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMC-Floods database: A high resolution press database on floods for the Spanish Mediterranean Coast (1960–2015)

Abstract: Abstract. Floods are the natural disaster that affects the greatest number of people and causes the highest economic losses in the world. However, some areas, such as the Mediterranean Coast of the Iberian Peninsula, are especially exposed to this natural hazard. The problem takes on even more relevance when a changing social dynamic is added to the natural context. With a view to accomplishing correct spatial planning in the light of the flood hazard, it is necessary to carry out an exhaustive analysis of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Some authors have suggested that the increase in the impact of floods is due more to socio-economic factors than to climate-related factors (Barredo et al, 2012;IPCC, 2012;Pérez et al, 2015a). In this context, the social factor involved in the risk equation established by Wisner et al (2004), vulnerability, is particularly relevant with respect to changes in the flood risk, but is very difficult to measure because social and environmental issues are at stake (Gil-Guirado et al, 2016). Despite there are a multitude of definitions of vulnerability (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that the increase in the impact of floods is due more to socio-economic factors than to climate-related factors (Barredo et al, 2012;IPCC, 2012;Pérez et al, 2015a). In this context, the social factor involved in the risk equation established by Wisner et al (2004), vulnerability, is particularly relevant with respect to changes in the flood risk, but is very difficult to measure because social and environmental issues are at stake (Gil-Guirado et al, 2016). Despite there are a multitude of definitions of vulnerability (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…De manera que, esta norma no tuvo ningún efecto práctico. Su período de vigencia coincidió con el proceso de expansión residencial más activo que ha vivido España en toda su historia (boom inmobiliario) que motivó el mayor incremento de la vulnerabilidad y exposición a la peligrosidad natural, particularmente a las inundaciones, en nuestro país (Burriel, 2008;Gil-Guirado et al, 2014;Pérez Morales et al, 2015). Habrá que esperar a la aprobación de la Ley del Suelo de 2008 para que una normativa urbanística aclarase la manera de acreditar la condición de riesgo de un territorio: la elaboración de un mapa (art.…”
Section: Evolución De La Geografía De Los Riesgos Enunclassified
“…Place/theme Author Climate risks Catalonia Western Mediterranean Llasat-Botija et al, 2006Llasat-Botija et al, 2007 Suarez, 1999García Martínez and Martín Ezpeleta, 2000Hernández Valera et al, 2003Llasat et al, 2009Domínguez-Castro et al, 2015Torrens Calleja et al, 2016Lopera Pareja, 2017Olcina Cantos, 2005Floods 1978 Spain (1960Spain ( -2015 Flooding in Vetania (Argentina) Danube floods from1012 to the present Calvo García-Tornel et al, 2001Mayer Suarez, 2002Olcina Cantos et al, 2004Pejenaute Goñi, 2008Cuello Gijón, 2010Rashid, 2011Pérez Morales and Gil Guirado, 2012Melinda, 2015Gutiérrez Abril, 2016Lang et al, 2016León González-Mazón, 2017Archer and Fowler, 2018Archer et al, 2019 Cuello Gijón, 2018 Barriendos et al, 2019Gil Guirado et al, 2019Ortuño Cano et al, 2019Prohaska et al, 2019 PAPER ACCEPTED. PRE-PRINT VERSION…”
Section: Themementioning
confidence: 99%